ID2 Inhibits Bladder Cancer Progression and Metastasis via PI3K/AKT Signaling Pathway - Mao, Weipu; Wang, Keyi; Sun, Si; Wu, Jianping; Chen, Ming; Geng, Jiang; Luo, Ming (Frontiers in Cell and Developmental Biology, 2021)
Background: Inhibitors of DNA-binding (ID) proteins are important regulators of cell proliferation and differentiation. The aim of this study was to evaluated the role of ID proteins in bladder cancer (BCa) and related molecular mechanisms. Methods: The TCGA database was analyzed for the expression and clinical significance of ID proteins. The expression of ID2 was determined by qRT-PCR, immunohistochemical staining and western blot. The role of ID2 was determined by CCK-8, colony formation, wound healing, transwell and xenograft tumor assays, and the potential mechanism of ID2 in BCa was investigated by RNA sequencing. Results: ID2 expression was significantly downregulated in TCGA database and clinical samples, and high ID2 expression was associated with low-grade tumor staging and correlated with better overall survival, disease specific survival and progress free interval. In vivo and in vitro experiments showed that knockdown of ID2 promoted proliferation, migration, invasion and metastasis of BCa cells, while overexpression of ID2 significantly inhibited cell proliferation, migration, invasion and metastasis. Mechanistically, ID2 acts as a tumor suppressor through PI3K/AKT signaling pathway to inhibit the progression and metastasis of BCa. Conclusions: Our results suggest that ID2 exerts tumor suppressive effects in BCa through PI3K/AKT signaling pathway, and altered ID2 expression can be used as a biomarker of BCa progression and metastasis.